EFEKTIVITAS ELEKTRONIK TILANG (E-TILANG) DALAM MENEGAKKANHUKUM PELANGGARAN LALU LINTASDI WILAYAH KEPOLISIAN DAERAH JAWA BARAT DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 22 TAHUN 2009TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Harris Fardillah; Hernawati RAS; Jafar Sidik (Iustitia Omnibus (Jurnal Ilmu Hukum), 2019)
The Republic of Indonesia is a State of Law. This concept of the state of law has been declared since Indonesia's independence and is included in the 1945Constitution of the Republic of Indonesia. As a state of law, every aspect of community life is regulated by law, including community activities related to traffic and road transport. UU 22/2009 was issued to provide a legal basis for community activities related to road traffic and transportation. UU 22/2009 also regulates the enforcement of traffic violations and road transport (LLAJ) through the e-ticketing system. The philosophy of the enactment of this e-ticket, is because there are many obstacles to the enforcement through manual ticketing, including the corrupt behavior of law enforcers. Based on this, the problem can be identified, namely the effectiveness of e- ticketing in suppressing traffic violations and what factors can affect the law enforcement of traffic violations through the use ofe-ticketing.This research uses a normative juridical approach, with the research specification is descriptive analytical and using primary and secondary data using data analysis on normative qualitative datas.The results of this study are the violation of road traffic violations using the E- ticketing system or mechanism has not been effective in suppressing violations of traffic and road transport under UU 22/2009 in the West Java Regional Police jurisdiction. This is because after theen force ment of Traffic and Road Transportation violations through the E-ticketing system was officially implemented on December16, 2016, the level of violations in the West Java Regional Police area has increasedand factors affecting the effectivity or ineffectivity of the enforcement of traffic violations and Road Transport through the E-Ticketing system, is influenced by its own regulatory factors (UU 22/2009), although formed in accordance with the principles of the legislation, but the value of sanctions has not been maximized. The law enforcement factors that are not yet consistent and consistent in enforcing the law, the factor of facilities or facilities, are ideally able to support e-ticketing, but the education factor on skills and adaptation to technology for officers can influence the effectiveness of e-ticketing. Community factors, because there are still some people who are undisciplined and are not afraid of sanctions for violations, because they think they can be resolved peacefully, and community cultural factors, related to social thought and social forces that determine how the law is used, avoided, or misused.